Antioxidant and Anticancer Functions of Protein Acyltransferase DHHC3 - Chandan Sharma; Martin E. Hemler (Antioxidants, 2022)
Silencing of DHHC3, an acyltransferase enzyme in the DHHC family, extensively upregulates oxidative stress (OS). Substrates for DHHC3-mediated palmitoylation include several antioxidant proteins and many other redox regulatory proteins. This helps to explain why DHHC3 ablation upregulates OS. DHHC3 also plays a key role in cancer. DHHC3 ablation leads to diminished xenograft growth of multiple cancer cell types, along with diminished metastasis. Furthermore, DHHC3 protein is upregulated on malignant/metastatic cancer samples, and upregulated gene expression correlates with diminished patient survival in several human cancers. Decreased primary tumor growth due to DHHC3 ablation may be partly explained by an elevated OS → senescence → innate immune cell recruitment mechanism. Elevated OS due to DHHC3 ablation may also contribute to adaptive anticancer immunity and impair tumor metastasis. In addition, DHHC3 ablation disrupts antioxidant protection mechanisms, thus enhancing the efficacy of OS-inducing anticancer drugs. A major focus has thus far been on OS regulation by DHHC3. However, remaining to be studied are multiple DHHC3 substrates that may affect tumor behavior independent of OS. Nonetheless, the currently established properties of DHHC3 make it an attractive candidate for therapeutic targeting in situations in which antioxidant protections need to be downmodulated, and also in cancer.